Value of endoscopic ultrasound guided fine needle aspiration biopsy in the diagnosis of solid pancreatic masses. Issue 2 (1st February 2000) - Voss, M; Hammel, P; Molas, G; Palazzo, L; Dancour, A; O'Toole, D; Terris, B; Degott, C; Bernades, P; Ruszniewski, P
Abstract : AIM: To assess the feasibility and diagnostic accuracy of endoscopic ultrasound guided fine needle biopsy (EUS-FNAB) in patients with solid pancreatic masses. METHODS: Ninety nine consecutive patients with pancreatic masses were studied. Histological findings obtained by EUS-FNAB were compared with the final diagnosis assessed by surgery, biopsy of other tumour site or at postmortem examination, or by using a combination of clinical course, imaging features, and tumour markers. RESULTS: EUS-FNAB was feasible in 90 patients (adenocarcinomas, n = 59; neuroendocrine tumours, n = 15; various neoplasms, n = 6; pancreatitis, n = 10), and analysable material was obtained in 73. Tumour size (⩾ or < 25 mm in diameter) did not influence the ability to obtain informative biopsy samples. Diagnostic accuracy was 74.4% (adenocarcinomas, 81.4%; neuroendocrine tumours, 46.7%; other lesions, 75%; p<0.02). Overall, the diagnostic yield in all 99 patients was 68%. Successful biopsies were performed in six patients with portal hypertension. Minor complications (moderate bleeding or pain) occurred in 5% of cases. CONCLUSIONS: EUS-FNAB is a useful and safe method for the investigation of pancreatic masses, with a high feasibility rate even when lesions are small. Overall diagnostic accuracy of EUS-FNAB seems to depend on the tumour type.